ONOMATOPE DALAM BAHASA INDONESIA - I Dewa Putu Wijana; Wira Kurniawati (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This article deals with structure, reference, and the use of onomatopoeic words, i.e. words containing sounds similar to the noises they describe. A close examination towards data collected from Kamus Besar Bahasa Indonesia, song lyrics, and the use of daily Indonesian, shows that the form and the referent of Indonesian onomatopoeic words are various, and they can be used literally or figuratively forproducing metaphorical and euphemistic expressions